Implementasi Restorative Justice di Indonesia sebagai Upaya Penyelesaian Sengketa Cyber Crime - Rafi Fadhlurrohman Arianto; Boedi Prasetyo (CV Rewang Rencang, 2024)
The resolution of cyber crime disputes through restorative justice has a positive impact, as the restorative justice approach shifts the focus from punishment to a process of dialogue and mediation aimed at creating a more just and balanced resolution, beneficial to both the victim and the perpetrator. This concept is rooted in the view that in every criminal act, the suffering experienced by the victim not only affects the victim itself but also impacts those around them, and even society and the nation on a broader scale. This study aims to examine the implementation of restorative justice as a solution to resolving cyber crime disputes. This research adopts a normative legal research method, focusing on the search for legal norms, concepts, and doctrines that can serve as the foundation for resolving legal issues. The techniques employed include approaches based on regulations and a contextual approach. In its analysis, the study uses qualitative analysis methods, focusing on the examination of collected legal documents. The research demonstrates that the implementation of restorative justice as an alternative in the criminal process in Indonesia is deemed effective, in line with the issuance of the Indonesian National Police Regulation No. 8 of 2021 on the Handling of Criminal Acts Based on Restorative Justice for the investigation process. This regulation serves as the foundation for the application of restorative justice principles in criminal cases. Restorative justice aims to provide restoration for the victim and accountability for the perpetrator. In this regard, the interests of both the victim and the perpetrator can be fulfilled. Therefore, the implementation of restorative justice as a resolution method can be conducted in Indonesia, with the goal of ensuring that victims regain their rights.